KONSELING INDIVIDUAL DALAM MENINGKATKAN SELF ESTEEM NARAPIDANA REMAJA - Ulandari Juwita; Rezki Hariko; Yeni Karneli (Institut Agama Islam Negeri Kerinci, Indonesia, 2023)
One of the problems facing juvenile inmates is low self-assessment due to life experiences that do not give an individual a positive impression. Good self-esteem is essential for all individuals, including juvenile Inmates. High self-esteem will trigger enthusiasm to change for the better, mainly when convicts are serving their sentences and are ready to face social life after returning to society later. This article discusses the role of guidance and Counseling in helping to increase self-esteem, namely through individual counseling services as a psychological intervention to create behavior change toward a practical daily life. The method used is a literature study from various references. The results of this study show the role of individual Counseling in increasing the self-esteem of juvenile Inmates through the stages and therapeutic procedures.